Thyroid dysfunction in metabolic syndrome: the ensuing storm - Ray, Subhashree; Sahu, Samir; Poddar, Anirban (International Journal of Research in Medical Sciences, 2016)
Background: Metabolic syndrome was initially defined as a constellation of hypertension, hyperglycemia, android obesity and gout. Thyroid dysfunction is characterized by altered thyroid stimulating hormone levels with normal or altered thyroid hormone levels. The aim of the study was to observe thyroid hormone levels and thyroid stimulating hormone levels in a cohort of patients with established metabolic syndrome and to report significant variations if any. Methods: 54 established cases of metabolic syndrome satisfying the IDF criteria were included in the study along with 54 ages and sex matched healthy controls. Results: Amongst the controls 92.6% were euthyroid, 5.6% were hypothyroid, 1.9% were subclinical hypothyroid. Among cases 64.8% were euthyroid. Thyroid dysfunction was found to be prevalent among 35.2% metabolic syndrome patients. Conclusions: Present study clearly reveals a higher incidence of thyroid dysfunction in metabolic syndrome. Metabolic syndrome and thyroid dysfunction are both considered as independent risk factors for cardiovascular disease. Therefore presence of both these entities in an individual increases the risk of a cardiovascular compromise. Hence assessment of thyroid function in metabolic syndrome might serve as a risk assesment tool to identify individuals predisposed to cardiovascular disease early, thereby resulting in a timely intervention.